2011
DOI: 10.1016/j.corsci.2011.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion inhibition of copper in neutral chloride media by a novel derivative of 1,2,4-triazole

Abstract: International audienceThe efficiency of a new corrosion inhibitor, the bis-(4-amino-5-mercapto-1,2,4-triazol-3-yl)-butane (BAMTB), on copper was investigated in an aerated 3% NaCl solution using various techniques. Voltammetry, chronopotentiometry and electrochemical impedance spectroscopy (EIS) were performed to evaluate the inhibition efficiency of BAMTB. The surface layers were also characterized by Raman micro-spectroscopy and by scanning electron microscopy (SEM) coupled with energy dispersive X-ray spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 65 publications
5
28
0
4
Order By: Relevance
“…Copper and its alloys, due to their high thermal and electrical conductivity, ease of fabrication and joining, mechanical duration, and corrosion resistance, have been extensively used in a wide variety of industrial sectors, such as electronics and electrical, pipeline, marine, automotive and manufacturing industries [1,2]. Nevertheless, copper alloys are prone to corrosion and localized corrosion in chloride-containing aqueous environments, causing structural failures [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper and its alloys, due to their high thermal and electrical conductivity, ease of fabrication and joining, mechanical duration, and corrosion resistance, have been extensively used in a wide variety of industrial sectors, such as electronics and electrical, pipeline, marine, automotive and manufacturing industries [1,2]. Nevertheless, copper alloys are prone to corrosion and localized corrosion in chloride-containing aqueous environments, causing structural failures [3].…”
Section: Introductionmentioning
confidence: 99%
“…These include thiazoles (benzotriazole), imidazoles, imidazolines, quinolines, thiols, Schiff bases, amino acids, naturally derived extracts, and pharmaceutical drugs. It has been demonstrated that these inhibitors, typically containing nitrogen, oxygen and sulphur hetero-atoms as major adsorption centres, are effective to inhibit corrosion of copper alloys in chloride solutions [2,[7][8][9][10][11][12][13], although some of them are inadequate to be both eco-friendly and high-efficient.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,4-Triazole and its amino derivatives, tetrazole,thiadiazole,pyrazole,imidazole and the corresponding derivatives have been studied as corrosion inhibitors of copper based material such as bronzes (Khiati et al, 2011). 1,2,4-Triazole (56) may exist in equilibrium between three forms: 1H-form(i), 1H-form(ii) and 4H-form as following, 1H-form(i) 1H-form(ii) 4H-form…”
mentioning
confidence: 99%
“…There is an extensive literature on the use of organic molecules as corrosion inhibitors [2][3][4]. In particular, azole, benzotriazole and their derivatives are the most investigated molecules as corrosion inhibitors [5,6]. Sol-gel coatings have been used as an alternative approach to provide a barrier layer against corrosion and protect the copper substrate.…”
Section: Introductionmentioning
confidence: 99%